Overt and covert postpartum urinary retention, risk factors and complications - a cohort study at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang, Malaysia - Zakaria, NH; Nusee, Zalina; Ab Rahman, Jamalludin; Ismail, Hamizah; Abdulwahab, Dalia F; Abdullah, Suhaiza; Awang, Mokhtar (Elsevier Ireland Ltd., 2012)
Introduction/Objective: The risk of postpartum urinary retention (PUR) varies between 0.5% and 14.1% of deliveries. It is higher among the Asian population with prolonged first and second stage of labour, epidural analgesia and previous history of PUR. The objectives were to determine the local incidence of PUR and to evaluate the risk factors and the outcome of PUR. Methods: A cohort study on women who delivered at HTAA from 1st January to 30th December 2011. The subjects were consented women who were stable, not eclamptic, no severe postpartum haemorrhage or medical illnesses that require routine bladder catheterization. Post void residual urine volume (PVRV) was measuredminimum of 6 h post delivery or when subject complaint of inability to pass urine. They were then catagorised into three groups: normal (PVRV < 150 mL), overt (symptomatic, PVRV > 150 mL) or covert (asymptomatic, PVRV > 150 mL). They were managed according to a standardised protocol till discharged. All subjects had a minimum of six months follow up or till the problem resolved. Results: There were 1000 women recruited. This preliminary result is on 414 women who had completed their follow up. The study subjects were mainly aged between 20 and 30 years (56.2%), Malay ethnic group (89.3%), obese (41.3%), low parity (80.9%) and had vaginal delivery (74.8%). There were two cases (0.48%) of overt and 13 cases (3.14%) of covert PUR. Majority of women (96.38%) had PVRV of <150 mL. There was no statistical different of PUR in relation to mode of delivery (P = 0.063), parity (P = 0.224), type of analgesic (P = 0.100), baby weight (P = 0.700) and time of voiding (P = 0.07) except for type of perineal wound (P = 0.01). Episiotomy causes significantly increased in PUR. Regarding covert PUR, 61.5% had urinary tract infection (UTI), 92.30% had an episiotomy wound and 69.23% resolved within 24 h. Both covert and overt PUR resolved spontaneously without complication. Conclusion: Risk of PUR was 3.62% which is compatible with others and had no serious complication. PUR was significantly associated with UTI and episiotomy.